The Impact of Information Technology on Personal Identity Rights and Privacy in the Modern World - Sweeta Khuram; Mursal Akrami; Fazila Akrami; Khatera Akrami; Tamanna Quraishi (Journal Electrical and Computer Experiences, 2024)
The intersection of information technology and personal identity rights presents a pressing challenge in the contemporary digital landscape. This study explores the impact of technology on personal identity rights and privacy perceptions among individuals affiliated with Women Online University. A convenience sample of 120 participants was recruited from the Women Online University community to participate in an online survey. The survey instrument included structured questions designed to assess participants' perceptions and attitudes regarding technology's impact on personal identity rights and privacy. Quantitative data analysis was conducted using descriptive statistics to summarize participants' responses and inferential statistics to examine relationships between variables. The results of the study reveal diverse perspectives among participants regarding the impact of technology on personal privacy and identity. While a significant proportion of respondent’s express confidence in existing legal protections for personal data, others harbor reservations about their efficacy. Additionally, the study highlights the nuanced relationship between technology and personal identity, with varying degrees of influence attributed to technological advancements. In conclusion, the findings underscore the need for robust regulatory frameworks and ethical guidelines to address the complex challenges posed by technological innovation to personal identity rights and privacy in the digital age. By fostering a deeper understanding of these issues, policymakers, technologists, and researchers can work towards ensuring the protection of individual autonomy and dignity in an increasingly digitalized society.